Morphological and Anatomical Variations of Roots, Leaves, Peduncles, and Peduncle Bracts in the Vriesea oligantha Complex (Bromeliaceae): Perspectives for Taxonomy - Silva, Kleber Resende [UNESP] (2020)
Vriesea is one of the genera of Bromeliaceae with the highest morphological diversity, including species of difficult recognition, many of them forming complexes, such as the Vriesea oligantha alliance. Morphological and anatomical comparative studies of vegetative and reproductive organs proved to be useful to solve such species complexes, besides indicating adaptive radiation.We analyzed comparatively the anatomy of roots, leaves, peduncles, and peduncle bracts of different populations found in rocky fields of Minas Gerais and Bahia, Brazil, with a taxonomic goal. In all the individuals studied the roots are composed of a velamen, a heterogeneous cortex, and a polyarch vascular cylinder, features that are common in the family. The leaves are covered by peltate trichomes and exhibit a hypodermis on both sides of the blade and a chlorenchyma composed of arm cells forming air lacunae between the collateral vascular bundles. The presence of subepidermal fiber strands in the leaves differentiates the populations ofMinas Gerais from those of Bahia. The peduncle has an atactostele with compactly arranged cells in the cortex and pith. The peduncle bracts exhibit a greater number of peltate trichomes on the abaxial surface and secretory channels occur in the mesophyll. A cluster analysis (UPGMA) based on leaf morphology and tank channel diameter generated a dendrogram with fourmain clusters, which correspond to V. lancifolia, V. oligantha, and V. pseudoligantha, plus another taxon. Intraspecific variations in the color and margin shape of leaves and peduncle bracts are interpreted as adaptive responses to environmental factors, mainly luminosity.